Characterization of nanostructured ZnO thin films deposited through vacuum evaporation - Alvarado, Jose Alberto; Maldonado, Arturo; Juarez, Héctor; Pacio, Mauricio; Perez, Rene (Beilstein Journal of Nanotechnology, 2015)
This work presents a novel technique to deposit ZnO thin films through a metal vacuum evaporation technique using colloidal nanoparticles (average size of 30 nm), which were synthesized by our research group, as source. These thin films had a thickness between 45 and 123 nm as measured by profilometry. XRD patterns of the deposited thin films were obtained. According to the HRSEM micrographs worm-shaped nanostructures are observed in samples annealed at 600 °C and this characteristic disappears as the annealing temperature increases. The films obtained were annealed from 25 to 1000 °C, showing a gradual increase in transmittance spectra up to 85%. The optical band gaps obtained for these films are about 3.22 eV. The PL measurement shows an emission in the red and in the violet region and there is a correlation with the annealing process.
Keywords: nanostructure; thin film; transmittance; vacuum evaporation; X-ray diffraction (XRD)